Uterine receptivity and embryo–uterine interactions in embryo implantation: lessons from mice. (1st June 2013) - Egashira, Mahiro; Hirota, Yasushi
Abstract: Implantation is a process of the first feto‐maternal encounter in the uterus. A competent blastocyst and a receptive uterus are critical for successful implantation. For an acquisition of uterine receptivity, the following conditions need to be satisfied in the uterine environments: the endometrial preparation with stromal proliferation and epithelial differentiation in the pre‐receptive phase and proper interactions between the uterus and blastocyst later in the phase. Focusing on these points and primarily referring to the mouse in vivo evidence, this review article has shown detailed molecular mechanisms for successful implantation.